2021
DOI: 10.4018/978-1-7998-6445-5.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Educator-Student Partnership

Abstract: The incorporation of web-based instruction within the educator-student partnership in the English language classroom today has taken on a pivotal role in complementing if not supplementing the traditional face-to-face teaching mode. In this study, the researchers set out to find out how pre-university students from various majors in Taylor's University, perceive Moodle as an online English Language learning environment that is able to capture some of the facets of learner autonomy amidst face-to-face interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…However, those with a high motivation level had a high autonomy level in using Moodle for building their English language skills. According to Tharumaraj, Rajandram and Singaram (2021), the interaction between lecturers and students is easier on Moodle as it advocates for knowledge development, skill exchange, learning independence, and collaboration. Interaction on Moodle aims to build an autonomous student, "who seeks knowledge, is constantly being researched, more so since [lecturer] -student [interaction] is continuously evolving with time" (Sevnarayan 2023b;Tharumaraj, Rajandram and Singaram 2021, 58).…”
Section: A Snapshot Of Related Work On Moodlementioning
confidence: 99%
See 1 more Smart Citation
“…However, those with a high motivation level had a high autonomy level in using Moodle for building their English language skills. According to Tharumaraj, Rajandram and Singaram (2021), the interaction between lecturers and students is easier on Moodle as it advocates for knowledge development, skill exchange, learning independence, and collaboration. Interaction on Moodle aims to build an autonomous student, "who seeks knowledge, is constantly being researched, more so since [lecturer] -student [interaction] is continuously evolving with time" (Sevnarayan 2023b;Tharumaraj, Rajandram and Singaram 2021, 58).…”
Section: A Snapshot Of Related Work On Moodlementioning
confidence: 99%
“…Students' responses further indicated that Moodle allows them the freedom to work independently. Seemingly, lecturers encourage student autonomy on the ENG321 Moodle site(Sevnarayan 2023b;Tharumaraj, Rajandram and Singaram 2021). An increase in dialogue from lecturers and a good design and structured Moodle site does narrow the TD gap(Moore 1993) between lecturers and students.…”
mentioning
confidence: 99%